STRENGTH AND DEFORMABILITY OF TWO-LAYER COMBINED METAL-COMPOSITE PLATES AND SHELLS WITH CONSIDERATION OF TEMPERATURE LOADS - Assoc. Prof. Dusmatov A. D. (Journals Park Publishing, 2024)
The paper studies the strength and deformability of combined two-layer slabs (plates) and shells. The influence of shrinkage and temperature loads on the stress-strain state of two-layer plates and shells is investigated. The influence of the adhesive joint flexibility of two-layer combined plates and shells on the stress-strain state is taken into account.
Keywords: Two-layer slab (plate), shell, reinforcing composite layer, shear modulus, shear function, tangential stress, displacement, temperature load, shrinkage of the composite layer.